Associations and interactions of clinical and genetic variables for type 2 diabetes mellitus in the mexican population - C.M. Martínez-Lara; L. Casas-Avila; M.L. Ramos-García; C. Castro-Hernández; D.A. Salazar-Piña; A. Hidalgo-Bravo; A.I. Barrera-Molina; O.C. Martínez- Ramírez (Human Nutrition & Metabolism)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by high blood sugar levels (hyperglycemia).It is among the top ten causes of death worldwide and involves non-modifiable (genetic risk variants) and modifiable factors (BMI, triglycerides and cholesterol). Methods: We included 199 subjects with T2DM and 213 subjects without T2DM, both groups of the Mexican population. Genotyping was determined using real-time PCR with TaqMan probes. We determined the associations and interactions of clinical and genetic variables for T2DM in the Mexican population using Multifactor-Dimensionality Reduction (MDR; Version 3.0.2). Results: The polymorphisms showed a strong association with the risk of suffering from T2DM when they occur additively and the interaction between clinical and genetic variables explains much of the weight of both factors in the etiology of the disease. Conclusion: The associations and interactions show that, regarding the risk of T2DM in this population, the most crucial is a BMI >24.9 kg/m2, followed by triglycerides >150 mg/dL and cholesterol <200 mg/dL; after this, ranked in importance for the risk of T2DM, are genetic polymorphisms in LEP, LEPR, FTO, and ADIPOQ in Mexican population.